KOSAKATA BAHASA JAWA SEBAGAI SALAH SATU PENGEMBANG KOSAKATA BAHASA INDONESIA (The Javanese Lexicon as One of Indonesian Lexicon Developer) - Wiwin Erni Siti Nurlina (Balai Bahasa Sulawesi Selatan, 2014)
This writing discusses form, meaning, and function of lexicon in Javanese language that absorbs to Indonesian language. Method used is descriptive qualitative and techniques are writing phonetically, selecting elements directly, and analyzing meaning component. The discussion shows that lexicon absorbed into Indonesian lexicon apply three ways, namely loaning, adaptation, and adaptation in whole. Lexicon categories are noun, verb, and adjective. Besides that, some lexicon changes in meaning (narrow or broaden) and some do not.